Production results of free range broiler chickens - Terčič, Dušan; Puhar, Jana; Vadnjal, Robert; Holcman, Antonija; Gašperlin, Lea; Rajar, Alenka; Žlender, Božidar (Acta Agraria Kaposváriensis, 1999)
The aim of this study was to compare growth performance and carcass characteristics from broilers raised in a free range system with those of broilers raised in a deep litter home. In the experiment 100 chickens of two commercial provenances were used. All the birds were raised in a deep litter house for the first four weeks. From then on they were divided into two groups, of which the free range group had free access to pasture ground. The chickens raised on pasture and the chickens raised in the deep litter house were slaughtered on the 56th day of age, after which certain carcass measurements were taken. The results obtained showed that the effects of genotype and sex on growth performance and carcass characteristics are much more important than the effects of the keeping system itself.